Pemberitaan Hutang Indonesia Dalam Bingkai Media Online - Fajriatul Kamelia; Lukman Nusa (Universitas Muhammadiyah Sidoarjo, 2018)
In Indonesia the ownership of online media is generally controlled only in the hands of a few people. The practice of this media conglomerate is considered a logical consequence of the development of the business world. Finally, the content of all media in Indonesia has become similar to each other and contains the interests of each media owner. For this reason, this study aims to see how online media Okezone.com and Viva.co.id in reporting Indonesia's debt reporting continues to roll throughout 2018. In analyzing, this study uses the analysis method of Zhongdang Pan and M. Gerald Kosicki framing for know how Okezone.com and Viva.co.id in framing reporting on Indonesian Debt in April 2018. The results showed that Okezone.com and Viva.coid lacked weight in framing the news. Okezone.com framed to show its alignment by posting news that constructed that Indonesia's debt was still at a safe level and debt was a natural thing. While Viva.co.id framed the news in favor of the Jokowi government. Viva.co.id emphasizes that the Indonesian government has a good ability to manage debt.